P370 Concomitant azathioprine prevents new-onset arthralgia after initiation of vedolizumab: A retrospective cohort study. (27th May 2021) - Kokkotis, G; Zampeli, E; Tzouvala, M; Giotis, I; Orfanos, P; Benetou, V; Stoupaki, M; Gizis, M; Kioulos, N; Kitsou, V; Leontidis, N; Leonidakis, G; et al.
Abstract: Background: Vedolizumab is a monoclonal antibody against the gut-homing integrin α4β7 that is being used for the treatment of moderate to severe Ulcerative Colitis (UC) and Crohn's Disease (CD). An increasing number of studies have reported new onset or reactivation of extra-intestinal manifestations (EIMs), among which arthralgia is the most prominent. Methods: We aimed to study the incidence, characteristics and possible predictors of arthralgia development in patients under treatment with Vedolizumab, in a retrospective cohort study in 3 IBD centers in Athens, Greece. UC and CD patients treated with Vedolizumab (n=115, men=50.4%, UC=70.4%, median duration of follow-up=9 months) or Infliximab (n=93, men=69.9%, UC=29%, median duration of follow-up=29.1 months) were recruited. For each participant the entry point for the study was the first day of drug administration while the endpoint was either the day of arthralgia occurrence, the day of drug discontinuation or the day of the last interview if the patient was still receiving the drug. The SPSS-23 statistical program was used for analysis. Results: Patients under Vedolizumab were at higher risk for new-onset (HR=4.76, P =0.001) and recurrent (HR=5.41, P =0.003) arthralgia compared to patients under Infliximab. New-onset arthralgia occurred in 20.9% while recurrent in 37.8% of 45 patients with a history of articular EIM. New-onset and recurrent arthralgias differed in certain characteristics. New-onset arthralgia involved peripheral joints in 91.7%, was milder, occurred shortly after Vedolizumab initiation (median drug exposure= 3 months, IQR=5 months) in patients in remission and remitted in 50% of cases. In multivariate Cox's proportional-hazards model new-onset arthralgia was significantly associated with extensive colitis (HR=2.91, 95%CI=1.04-8.12). Of 15 patients with concomitant treatment of azathioprine no one manifested new-onset arthralgia (X 2 P = 0.03, Fisher's exact test P=0.038). Similarly, no patient with a history of appendectomy manifested new-onset arthralgia (n=12, X 2 P = 0.067, Fisher's exact test P=0.12). No predictors were identified for recurrent arthralgia. No patients discontinued vedolizumab due to arthralgia. Conclusion: Vedolizumab treatment may be associated with the temporal manifestation of arthralgias. Patients under Vedolizumab with extensive ulcerative colitis have a higher risk of developing new-onset arthralgia, whereas, concomitant treatment with azathioprine and a history of appendectomy appears to have a prophylactic effect. This effect could be indicative of a distinct pathophysiological lymphocyte-mediated mechanism.